Effect of the WTO Trade Facilitation Agreement on Trade in Environmental Goods - Ayufi, Nori (Universitas Negeri Gorontalo, 2026)
The World Trade Organisation’s Trade Facilitation Agreement (WTO TFA) is designed to streamline cross-border trade by reducing administrative delays and costs through improved border procedures. Despite this goal, TFA's specific influence on the trade of environmental goods has not yet been empirically investigated. Therefore, this study fills the gap by using panel data from 2017 to 2021 and applying random-effect estimation to investigate the relationship between TFA and trade of environmental goods in developing and least-developed countries. The outcome indicates that there is no evidence the TFA impacts the trade of environmental goods. The result is robust across alternative estimation methods, subsample analysis, and the use of different standard errors. One possible explanation is that TFA implementation may not be sufficiently targeted towards environmental goods, or the commitment under the TFA does not accurately capture actual implementation. In contrast, control variables such as GDP, population, and industrialisation level significantly impact the trade of environmental goods.